Clinico-demographic profile of deceased patients with coronavirus disease in a tertiary care centre of central India - Patle, Rupali A.; Jadhao, Ashok R.; Dhengre, Priya B.; Dhoble, Manjusha A. (International Journal Of Community Medicine And Public Health, 2021)
Background: The covid pandemic started from Hubei, Wuhan in December 2020 then covered many other countries including India. Understanding the demographic and clinical characteristics of deceased COVID-19 patients could inform public health interventions focusing on preventing mortality due to COVID-19. The present study was done with the objective of studying the socio-demographic and clinical profile of deceased patients with coronavirus disease. Methods: This is a hospital based cross-sectional study on 1190 deceased patients of coronavirus disease in a tertiary care hospital of central India which is a dedicated covid hospital from 11 March 2020 to 28 February 2021. Socio-demographic and clinical characteristics of deceased patients were recorded. Results: Overall case fatality rate was 13.24%. Maximum number of deaths occurred in the month of August 2020 and September 2020 were 372 (31.26%) and 477 (40.08%). It was higher in the males 791 (66.47%) as compared to females 399 (33.53%), but the difference was not significant. The most common symptom was fever on hospitalization 924 (77.65%), followed by generalized weakness 771 (64.79%). 352 (29.58%) patients died within 24 hours of the admission to hospital. Hypertension and type 2 diabetes mellitus were the most prevalent morbidity in 557 (46.80%) and 357 (30.00%). It was found that 232 (19.50%) deceased patients had oxygen saturation less than 50% on admission. Conclusions: Higher age and presence of co-morbidities at the time of admission were significantly associated with mortality.